Para além do centro histórico: valores e sentidos do patrimônio cultural edificado de Santa Maria/RS - Silva, Manuela Ilha (2015)
Ownership of Cultural Heritage for a community is a prerequisite for it to exist as an element that confirms memories and stories and especially to make sense for a particular social group. To transcend the condition of materiality and to earn meanings that do not end in itself, in the case of the material heritage, the building must be holder of culturally assigned values that make it identifiable as heritage. From this place, the issue of the present study subsidizes up: how the community perceives and assigns value to material cultural heritage from outside the concentration of the historic center of the city of Santa Maria/RS? This area covers significant volume of buildings with heritage interest of the city, for example, the Railway Stain, the Metropolitan Cathedral and most of Santa Maria s acquis Art Deco. The space, as imagined and institutionalized as a region that has copies of cultural heritage material, hosted the city's growth in its different phases. However, the city is home to other buildings with potential asset value which go beyond the imagined line and legally defined as asset protection space, which implies new "places of memory" in the city. Based in the questioning of values assigned to monuments by Riegl (2013) and rescued by Meira (2008), this study seeks to identify ways of assigning meaning to the Material Cultural Heritage by the community of Santa Maria / RS in regions outside the historic center. From a representative sample of these examples, we seek to identify the ways of heritage ownership and highlight possible strategies to appreciate these memories. As input to discuss these questions, this study is based on methodologically-bibliographic and documentary research, needed to support the development of community approach instrument that, in this case, is the questionnaire. In this survey, made up of ten copies, there are both isolated and residential buildings as architectural complexes and editions of urban importance. All of them share potential heritage value and peripheral location in relation to the "historical center". Each copy was analyzed from the discussions proposed by Riegl (2013) and as a whole, provide a discussion that reaches all discussed values. The results showed that the central region is ratified in the collective imagination as a space which concentrates local heritage. Assigning values to those outside buildings in the center is discreet, with historical valuations and seniority, without the perceived potential of heritage building for other uses, for example. In conclusion, by the urgency of appreciation actions of this cultural heritage.